A Methodology to Plan Wireless Network in Indonesian Rural Areas - Nazmia Kurniawati (Politeknik Negeri Jakarta, 2023)
Wireless telecommunication networks have been widely implemented in Indonesia. However, the planning methodology hasn’t been intensively studied. In this paper, we proposed a novel methodology for wireless local area network planning in Indonesian rural area. Our proposed method consists of eleven steps of work emphasizes the ease of implementation, market survey consideration, Indonesian Government standard application, and free tools usage optimization. At the end, an example of a network design created by following the proposed methodology for Sebira Island is presented.